Refractive hard x-ray vortex phase plates - Seiboth, Frank; Kahnt, Maik; Lyubomirskiy, Mikhail; Seyrich, Martin; Wittwer, Felix; Ullsperger, Tobias; Nolte, Stefan; Batey, Darren; Rau, Christoph; Schroer, Christian G. (Optics Letters, 2019)
In this Letter, we report on the creation of hard x-ray beams carrying orbital angular momentum of topological charge −ℏ and −3ℏ at a photon energy of 8.2 keV via spiral phase plates made out of fused silica by ultrashort-pulsed laser ablation. The phase plates feature a smooth phase ramp with a 0.5 μm nominal step height and a surface roughness of 0.5 μm. The measured vortex beams show submicrometer-sized donut rings and agree well with numerical modeling. Fused silica phase plates are potentially suited to manipulate the electromagnetic field in highly intense x-ray beams at x-ray free-electron laser sources.
CRIS-Team Scopus Importer:2023-04-20